The role of statistical programs in research (Eurasian Journal of Philology Science and Education, 2016)
Statistical software are specialized computer programs for analysis in statistics. As quantitative research grows, application of statistical software (SS) becomes a more crucial part of data analysis. Researchers are experiencing a transition from manual analysis with paper to more efficient digital/electronic analysis with statistical software (SS). In this article the authors examine the program in terms of efficiency of use in the humanities.
Keywords: statistic; computer programs; research; quantitative research